Relative efficiency of plantation companies in Malaysia: a financial ratio-based data envelopment analysis approach - Abdul Wahab, Abdul Hamid; Abdul Razak, Dzuljastri (South East Asia Journal of Business Economics and Law, 2015)
This study examines the relative efficiency of 31 plantation companies in Malaysia based on data for the first three cumulated quarters of 2012 (January - September). The study applies an adopted version of Data Envelopment Analysis (DEA). DEA is a tool used to weigh the inputs/outputs and measure the relative efficiency of decision-making units. This research adopts an output-oriented form of DEA based on financial ratios without the utilization of inputs. The innovative adopted DEA model provides a comprehensive decision on a company’s efficiency by taking into account various financial ratios all together and combining them into a single measure of efficiency. The results show that out of the 31 plantation companies in Malaysia, only five (16.13%) proved to be efficient. Also, it is found that the higher a company’s financial ratio in relation to the equivalent ratios of other companies, the higher the efficiency score of that company.